An optimal variational iteration method - Turkyilmazoglu, M. (Applied mathematics letters, 2011)
The variational iteration method is studied in the present work. The classical variational iteration method is improved and extended by introducing a new concept of a convergence accelerating parameter. A rigorous approach is later proposed for optimally determining the value of the convergence accelerating parameter. The consequences of the novel optimal variational iteration method are discussed through an application.